The Association of cagA, vacA, babA2, babB and oipA of Helicobacter pylori with Risk of Gastric Carcinoma Development - Zainab H. Alsaadi; Nada Kadlim Hindi; Ali H. Al Marzoqi; Mojtaba Memariani; Maryam Kohansal; Abdolmajid Ghasemian (Journal of Advanced Biomedical Sciences, 2022)
Background & Objective: Helicobacter pylori (H. pylori), carried by more than half of the world population, is a major cause of chronic duodenal and gastric ulcers, gastritis and carcinoma. Colonization and toxin production include major virulence traits of H. pylori. The aim of this study was to assess the existence of H. pylori and virulence factors among patients with risk of gastrointestinal carcinoma (GC) in an Iraqi population. Materials & Methods: During May 2016- October 2020 in Babylon, Iraq, a total of 500 biopsy samples were obtained from gastric tissue of patients with GC, gastritis, duodenitis, duodenal ulcer and gastric ulcer and cultured onto the Brucella agar. H. pylori isolates were identified using conventional biochemical and molecular tests. Molecular identification was conducted by amplification of glmM gene using the polymerase chain reaction (PCR) technique. The adhesin (babA2, babB and oipA) and toxin (cagA and vacA) genes were also amplified using PCR technique.